1992
DOI: 10.3758/bf03202720
|View full text |Cite
|
Sign up to set email alerts
|

Age of acquisition, not word frequency, affects object naming, not object recognition

Abstract: Word frequency is widely believed to affect object naming speed, despite several studies in which it has been reported that frequency effects may be redundant upon age of acquisition. We report, first, a reanalysis of data from the study by Oldfield and Wingfield (1965), which is standardly cited as evidence for a word frequency effect in object naming; then we report two new experiments. The reanalysis of Oldfield and Wingfield shows that age of acquisition is the major determinant of naming speed, and that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
281
3
19

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 326 publications
(334 citation statements)
references
References 41 publications
31
281
3
19
Order By: Relevance
“…Logie (1981a, 1981b) found no evidence for an AoA effect on visual or auditory word recognition thresholds, which suggests that observed AoA effects in naming and lexical decision must result from processes operating after lexical access. Morrison et al (1992) found that AoA affected picture naming latencies, but not performance on a living versus a nonliving categorization task on the same pictures, which suggests that the AoA effect in naming arises from postsemantic processes. The most likely locus of the AoA effect is, therefore, at the stage of retrieval of lexical phonology.…”
Section: Are Effects Of Aoa In the Ldt Dependent On The Retrieval Of mentioning
confidence: 94%
See 1 more Smart Citation
“…Logie (1981a, 1981b) found no evidence for an AoA effect on visual or auditory word recognition thresholds, which suggests that observed AoA effects in naming and lexical decision must result from processes operating after lexical access. Morrison et al (1992) found that AoA affected picture naming latencies, but not performance on a living versus a nonliving categorization task on the same pictures, which suggests that the AoA effect in naming arises from postsemantic processes. The most likely locus of the AoA effect is, therefore, at the stage of retrieval of lexical phonology.…”
Section: Are Effects Of Aoa In the Ldt Dependent On The Retrieval Of mentioning
confidence: 94%
“…Currently, there is no firm evidence of AoA effects in any lexical processing task that does not involve the retrieval of phonology. Admittedly, there have been only few attempts to look for possible AoA effects in tasks in which phonological variables have no major influence; for example, Morrison et al (1992) found no effect of AoA in the semantic categorization ofpictures, even when a clear AoA effect on the naming latencies to the same pictures was observed. However,additional studies ofthe possible effects of AoA in other lexical processing tasks will be required in order to investigate this further.…”
Section: Why Was the Aoa Effect Not Eliminated In Experiments 2-5?mentioning
confidence: 99%
“…As explained in the Introduction, two possible loci of AoA effects in picture naming have been suggested: lexical-semantic (Belke et al, 2005;Johnson & Barry, 2005) and lexical phonological encoding processes (Chalard & Bonin, 2006;Morrison and Ellis, 1995;Morrison et al, 1992). Different amplitudes between early-and late-acquired words were observed in four distinct time periods.…”
Section: Aoa Effectmentioning
confidence: 95%
“…However, the reliably of lexical frequency effects has been challenged since effects of word AoA have also been reported (e.g., Bonin, Fayol, & Chalard, 2001;Bonin, Chalard, Méot, & Fayol, 2002;Chalard, Bonin, Méot, Boyer, & Fayol, 2003;Morrison, Ellis, & Quinlam, 1992;Morrison & Ellis, 1995). Especially, when those variables are operationalised following the recommendations made by Zevin and Seidenberg (2002) 1 , reliable AoA effects were reported on conceptually driven spoken production (as in picture naming paradigms, Bonin et al, 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation